2010
DOI: 10.1590/s1806-37132010000500002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores de risco para sibilância no primeiro ano de vida

Abstract: Objective: To determine the prevalence of and the risk factors for wheezing in infants under one year of age and residing in the city of Porto Alegre, Brazil. Methods: This was a cross-sectional study and is part of a multicenter, multinational project. The parents or legal guardians of the infants were interviewed at primary health care clinics or during home visits. We used a standardized questionnaire, validated for use in Brazil. Potential risk factors were assessed by means of a Poisson regression model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
4
16
1
13
Order By: Relevance
“…The lack of standardization in the definition of wheezing, the type of study and the age range of these studies may be the cause of such variation 12 . In the present study, the prevalence of wheezing episodes during the first year of life was 57.5% compared with studies done in the city of Porto Alegre, Rio Grande do Sul, Brazil pointing its prevalence as 61% 5 .…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…The lack of standardization in the definition of wheezing, the type of study and the age range of these studies may be the cause of such variation 12 . In the present study, the prevalence of wheezing episodes during the first year of life was 57.5% compared with studies done in the city of Porto Alegre, Rio Grande do Sul, Brazil pointing its prevalence as 61% 5 .…”
Section: Discussioncontrasting
confidence: 50%
“…In this research it was observed that there was a predominance of male infants whistling as has been shown by several researchers [5][6][7][8][9][10] , but cal-culated the prevalence ratio was not significant. The reason for this gender difference is based on lower airway caliber male relative to the female gender 13 , this relationship, which is reversed as the child reaches adolescence.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Verificaram-se reinternação da criança pelo mesmo episódio em 2,1% dos casos e reinternação da mesma criança por outro episódio em 24,8% A idade mostrou-se inversamente relacionada à prevalência de sibilância nas crianças Guarani. A precocidade na apresentação de sibilân-cia em crianças foi descrita por diversos autores em populações carentes atendidas em serviços públicos de saúde em cidades do Sul e Sudeste do Brasil 2,20,21 . Em estudo em pacientes atendidos em unidades básicas de saúde em São Paulo, encontrou-se uma prevalência elevada de sibilância, com quase metade dos lactentes apresentando pelo menos um episódio de sibilância já no primeiro ano de vida 2 .…”
Section: Resultsunclassified